Maryja jako grecko-rzymski ideał kobiety - Zawadzki, Robert Krzysztof (Verbum Vitae, 2021)
The article discusses the Graeco-Roman moral, religious, and literary context within which Mary’s cult was expressed and developed. It offers an analysis of Mary’s titles used together with her name, focusing on their relationship to the same aspects of the Graeco-Roman culture, and how the Mother of God as the Virgin, Lady of Consolation, Lady of Sorrows, and Madonna was perceived by the pagans. It demonstrates that this extolling of Mary’s virtues, however unlikely when applied to her, did have some precedents in the culture of Greeks and Romans who were prepared to accept Mary’s cult. The article sheds light on the early development of Mary's cult to seek to relate doctrine or dogma about Mary to the Graeco-Roman surroundings.